Tuition, debt, and human capital - Rajashri Chakrabarti; Vyacheslav Fos; Andres Liberman; Constantine Yannelis (Federal Reserve Bank of New York, 2020)
This paper investigates the effects of college tuition on student debt and human capital accumulation. We exploit data from a random sample of undergraduate students in the United States and implement a research design that instruments for tuition with relatively large changes to the tuition of students who enrolled at the same school in different cohorts. We find that 10,000 in higher tuition causally reduces the probability of graduating with a graduate degree by 6.2 percentage points and increases student debt by 2,961. Higher tuition also reduces the probability of obtaining an undergraduate degree among poorer, credit-constrained students. Thus, the relatively large increases in the price of education in the United States in the past decade can affect the accumulation of human capital.
Keywords: D14; H52; H81; I23; J24; 330; tuition; student debt; human capital; credit constraints